Textbook of plant chemistry - Pooja (Discovery Publishing House, 2011)
Plants are a major group of living things (about 300,00 species), including familiar organisms such as trees, flowers, herbs, and ferns. Aristotle divided all living things between plants, which generally do not move or have sensory organs, and animals. In Linnaeus' system, these became the Kingdoms Vegetabilia (later Plantae) and Animalia. Since then, it has become clear that the Plantae as originally defined included several unrelated groups, and the fungi and several groups of algae were moved to new kingdoms. However, these are still often considered plants in many contexts. Indeed, any attempt to match "plant" with a single taxon is doomed to fail, because plant is a vaguely defined concept unrelated to the presumed phylogenic concepts on which modern taxonomy is based.--Provided by publisher.